Principle of Good Faith in Holding the Third General Meeting of Shareholders for Minority Shareholders - Eriz Syawaldi Sitompul; Iwan Erar Joesoef; Suherman Suherman (International Journal of Sociology and Law, 2025)
The purpose of this study is to examine the principle of good faith , which is a fundamental aspect of corporate governance, which ensures fair treatment for all shareholders, including minority shareholders. This study examines the application of good faith in the third General Meeting of Shareholders (GMS) in relation to the protection of minority shareholders, focusing on Decision Number 389/PDT.P/2019/PN.CKR. This study aims to analyze the court's reasons behind the issuance of the Niet Ontvankelijke Verklaard decision at the third GMS and to evaluate the legal protection mechanisms available to minority shareholders. This study uses a normative juridical approach, by analyzing legal norms and judicial precedents related to corporate governance and shareholder rights. The research findings reveal that minority shareholders often face legal uncertainty and procedural disadvantages in GMS decisions, especially when the principle of good faith is not upheld. The court's rejection of the third GMS application highlights the need for a more comprehensive legal framework to protect the interests of minority shareholders and ensure a fair corporate decision-making process. This study contributes to the corporate governance discourse by emphasizing the importance of procedural fairness and legal certainty in shareholder meetings